Beginning SQL Server 2005 for Developers - Dewson, Robin (Apress, 2012)
Beginning SQL Server 2005 for Developers is for those people who see themselves as becoming either developers, database administrators, or a mixture of both but have yet to tread that path with SQL Server 2005. Whether you have no knowledge of databases, or have knowledge of desktop databases such as MS Access, or even come from a server-based background such as Oracle, this book will provide you with the insight to get up and running with SQL Server 2005. Right from the start, your basic knowledge will be expanded, and you will soon be moving from a perceived beginner through to a competent and professional developer. It is the aim of this book to cater to a wide range of developers, from those who prefer to use the graphical interface for as much work as possible to those who want to become more adept at using SQL Server 2005’s programming language, T-SQL. Where practical, each method of using SQL Server 2005 is demonstrated, explained, and expanded so that you can evaluate what works best in your situation.